2019
DOI: 10.3390/pharmacy7030109
|View full text |Cite
|
Sign up to set email alerts
|

Financial Incentive Required for Pharmacy Students to Accept a Post-Graduation Position in Rural and Undesirable Pharmacy Settings

Abstract: Background: It has been estimated that in 2018, 20% of pharmacy students were unemployed following graduation. However, many pharmacy positions go vacant each year, with the majority of these positions existing in rural areas. Methods: Pharmacy students completed a one-time, anonymous, online questionnaire. Measures of interest included: subject characteristics and preference in a variety job offers. Discrete Choice Experiment methodology of questionnaire design was used and Conditional Logit models were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Among respondents, we can see that students who were the only child in the family, female, with an urban background, or from a more wealthy family were placed stronger values on work location than their counterparts. This nding is consistent with a previous study in the United [25]. When designing a more effective policy implementation to attract pharmacy students to work in the rural areas, it would be important to take into account their backgrounds, e.g.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Among respondents, we can see that students who were the only child in the family, female, with an urban background, or from a more wealthy family were placed stronger values on work location than their counterparts. This nding is consistent with a previous study in the United [25]. When designing a more effective policy implementation to attract pharmacy students to work in the rural areas, it would be important to take into account their backgrounds, e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Both a literature review and qualitative studies were conducted to ensure that the attributes and levels included are the most meaningful for respondents. Firstly, we identify 9 attributes from a literature review, including monthly income, work environment, work location, bianzhi (which refers to the established posts and can be loosely regarded as state administrative sta ng), workload, training opportunity, career development opportunity, management style, and welfare [22][23][24][25][26]. Next, we consulted 3 experts and based on their opinion, the bianzhi, workload, welfare, and career development opportunity were removed; on the other hand, years to the promotion was suggested to be added and the monthly income level was suggested to be adjusted.…”
Section: Attributes and Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, there have been two DCE studies exploring the job preferences of pharmacy students. The first study identified six attributes and surveyed 283 students in total from the United States and Canada [ 26 ]. This study found significant differences between states and provinces in the job preferences of pharmacy students.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps unexpectedly, the profession now faces at best an equilibrium in less-desired states and rural areas and an oversupply of pharmacists in the most-desired metropolitan areas of the country. 95 Many demand-side factors have not fully manifested according to predictions from 1 to 2 decades ago, such as new practice roles and payment for pharmacists’ services as health educators. In sum, the prediction did not materialize.…”
Section: Data Synthesismentioning
confidence: 99%